Effectiveness of Structured Teaching Program on Knowledge of Antenatal Mothers Regarding Selected Newborn Danger Signs - Manjula, T.; Sayee, Gowri (Indian Journal of Nursing Sciences, 2024)
Aim: The aim of the study was to assess the existing knowledge of antenatal mothers regarding selected newborn danger signs and to find out the effectiveness of structured teaching program on knowledge regarding selected newborn danger signs among antenatal mothers. Design: Quasi-experimental one group - pre-test post-test design without a control group. Setting: Participants were recruited from Fortis Hospital, Bannerghatta Road, Bengaluru. Participants: Nonprobability purposive sampling techniques were adopted to select the 60 antenatal mothers. Methods: Pre-test was conducted to assess the knowledge of antenatal mothers regarding selected newborn danger signs using structured knowledge questionnaire. Administration of structured teaching program on selected newborn danger signs is done for antenatal mothers. Day 7 post-test was done using the same structured knowledge questionnaire. Results: The study revealed that structured teaching program on prevention and management of selected newborn danger signs among antenatal mothers was effective in enhancing knowledge of antenatal mother as indicated by significant 0.05 level of significance. There was a statistically significant association between the knowledge and selected demographic variable of antenatal mothers. Conclusion: Structured teaching program was effective in increasing the knowledge of antenatal mothers regarding selected newborn danger signs.